Efeitos do método multigestos® na intervenção dos transtornos dos sons da fala - Gubiani, Marieli Barichello (2021)
This research sought to verify and compare the effects of intervention with the support of the MultiGestos® Method (AZEVEDO; SILVA, 2016; SILVA, AZEVEDO and GUBIANI, 2021) in phonologically-based Speech Sound Disorders (SST). From a previous survey, 5 subjects were selected, aged between 4:7 and 7:6 years. The subjects made up a group that underwent a phonological therapeutic approach with the support of the MultiGestos® Method. The subjects were evaluated in two moments, pre-therapy and post-therapy with the following instruments: Orofacial Myofunctional Assessment with Scores (AMIOFE; FELÍCIO; FERREIRO, 2008), Auditory Vocabulary Test (TVAud-A33o – CAPOVILLA et al., 2011), INFONO (CERON, 2015), Children's Naming Test (TIN) short version (SEABRA et al., 2012), Articulatory Awareness Assessment (CONFIART - SANTOS et al., 2009), Word and Pseudoword Repetition Test (TRPP – Seabra, 2012) and - Phonological Awareness Test by Oral Production (PCFPO - SEABRA; CAPOVILLA, 1998). The instruments for Assessment of orofacial praxis skills – The Orofacial Praxis Test (BEARZOTTI et al, 2007), Dynamic assessment of speech motor skills (GUBIANI, 2016) were applied only in the pre-therapy period. The subjects received speech therapy with the support of the MultiGestos® Method, according to the changes presented in their phonological system and phonetic inventory. After the intervention period, the data were analyzed and there was an improvement in the phonological system, phonetic inventory and in the severity classification of the phonologically-based TSF for S1. The other subjects of this research showed a numerical evolution regarding the severity of the TSF.